(untitled) - Mitchell, Kennedy (Hoboken, 2003)
Single stock futures are an incredibly important new financial instrument for managing risk. Kennedy Mitchell provides an outstanding and easy-to-read explanation of these new products for either an expert futures user or for someone learning about futures markets for the first time.
Keywords: Single stock futures,Speculation,Futures